EFFECT OF TREATMENT ON GERMINATION OF SEEDS OF LAURUS NOBILIS L NATURAL STANDS IN LATAKIA (KASSAB) AND HAMA (ALGHAB). (Latakia University Journal -Biological Sciences Series, 2023)
This research carried out in during (2018 -2019) in Latakia (kassab) and Hama (AL ghab) Research carried out in (2018-2019) in two different geographical areas and climatic in Latakia (kassab) and Hama(ALghab).Laurus  nobilis, L of  fruits were collected from forest stands in the fall of (2018)Experiment was applied using (1296) seeds   which were divided into five groups at fallows:(1)Control, (2) cold  stratified at +4 degrees for (25-50) days,(3) Scarification  mechanical,(4) Seeds without  pericarp and epicarp  , (5) Treatment of GA3 (1000 - 3000) ppmStudy showed as follow:Treatment  seed without pericarp and epicarp  to surpass of rest treatments with rate (81.48-88.88)%  while in treatment of GA3 (1000-3000)ppm germination  increased from (77.77)% to (70.37)% due to  increasing  acid  concentration  and can play a negative role in stimulating  pulp  on germination.Percentage or germination increased from (14.8)%  in Scarification mechanical to (88.88)%  of treatment ( Seeds   without  pericarp and epicarp,  Results suggested that seed dormancy was mainly due to pericarp and epicarp  perhaps inhibitors linked to seed coat.